2018
DOI: 10.1007/s41999-018-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life as a predictor of mortality in heterogeneous samples of older adults

Abstract: Health-related quality of life (HRQoL) was measured in eight cohorts of older adults with multimorbidities and various functional, cognitive, psychological or social disabilities. • 15D, a generic HRQoL predicted independently and significantly the 2-year survival in the total sample. • However, 15D did not predict mortality in samples of spousal caregivers and lonely older adults. • In older populations suffering from psychological and social impairments such as caregiver burden or loneliness HRQoL may not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…Our ndings are in line with a previous study that used pooled analysis [29] of eight heterogenous Finnish cohorts using the 15D HRQoL measure and included a wide range of both community-dwelling participants with or without morbidity, such as cardiovascular disease, dementia, and hospitalized patients with delirium. They also found that the 15D HRQoL measure was associated with two-year survival, with a slightly higher hazard ratio than that found in our study (HR per 1-SD = 0.44, 95% CI 0.40 to 0.48) [29]. These differences may relate to their inclusion of patient groups in generally poorer health, while our systematic review focused on the community dwelling population.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our ndings are in line with a previous study that used pooled analysis [29] of eight heterogenous Finnish cohorts using the 15D HRQoL measure and included a wide range of both community-dwelling participants with or without morbidity, such as cardiovascular disease, dementia, and hospitalized patients with delirium. They also found that the 15D HRQoL measure was associated with two-year survival, with a slightly higher hazard ratio than that found in our study (HR per 1-SD = 0.44, 95% CI 0.40 to 0.48) [29]. These differences may relate to their inclusion of patient groups in generally poorer health, while our systematic review focused on the community dwelling population.…”
Section: Discussionsupporting
confidence: 90%
“…Two published articles of De Buyser et al reported the results of the same populationbased cohort study [41,42], three published articles by De Salvo et al and Fan et al were from the same study and included participants enrolled in the Veterans Affairs Ambulatory Care Quality Improvement Project [24,43,47], two published studies of Mold et al and Lawler et al used the same communitydwelling cohort [57,61], two published studies of Higueras-Fresnillo et al and Otero-Rodriguez et al were from the same Spanish cohort [52,67], two published studies of Feeny et al and Kaplan et al were from the same Canadian cohort [48,55]; and Myint et al published three articles [26,64,65] with different perspectives on the same population-based study. Additionally, Liira et al's study [29], included eight individual cohorts, however, only ve of the cohorts met the inclusion criteria for this current systematic review, and thus are shown in Table 1.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Declining functional levels in older adults may be directly or indirectly related to their quality of life, major health problems, and mortality. 26,27) Assessment of the independence level of functions helps healthcare personnel to provide appropriate treatment, care, and counseling services by identifying the needs of older individuals and taking necessary measures. 28) This study adapted the Lawton-IADL, which is used to determine the IADL level in older adults, and analyzed its validity and reliability.…”
Section: Discussionmentioning
confidence: 99%